The Relationship between social capital and farm household consumption expenditure in conflict-vulnerable areas of Mindanao - Predo, Canesio D.; Menz, Kenneth (2017)
The improvement of farm income generating capacity via social capital enhancement is a common goal in many community-based rural development projects. Yet, there are extremely limited studies empirically linking economic benefits and social capital, especially at the level of individual farm households. This paper aims to estimate empirically this relationship using farm household consumption expenditure as a proxy for farm income in the case of conflict-vulnerable areas in Mindanao, Philippines. Social capital enhancement is thought to be especially relevant in such areas, and the results in this paper engender more confidence in such an approach.
A reduced-form model was estimated using ordinary least squares method and household survey data of 185 respondents. The model results indicate positive correlation between household social capital and farm household consumption expenditure. Specifically at the current level of consumption expenditure in the study households, social capital was found to have an economic value of PhP 481 per household per month, or 14% of current household consumption expenditure. This finding supports the idea of promoting social capital as a component of livelihood improvement strategies for conflict areas in Mindanao, especially strategies with knowledge transfer orientation like agricultural extension.
Keywords: Agricultural income